Integration of Traditional Kerinci Games in Elementary School Physical Education: Impacts on Cooperation and Discipline (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
This preliminary study examined the impact of integrating three traditional Kerinci games, including Rakalah, Conce, and Prakeja, into elementary school physical education learning on student cooperation and self-discipline. A total of 30 students in grades IV and V participated in 16 meetings within a single-group pretest-posttest design. Cooperation and self-discipline were measured using a questionnaire that had been tested for its validity and reliability, then analyzed using a paired t-test and Cohen's d effect size. The cooperation score increased from 38.77 to 45.60, while the self-discipline score increased from 38.33 to 42.40. This study is expected to enrich the evidence for cultural pedagogy, showing that local games can serve as a vehicle for character education in physical education learning. Teachers can use traditional games as core activities and as part of P5 activities to practice role coordination, rule adherence, and value reflection. However, because the design lacked a control group and the measurements were self-report-based, the findings need to be confirmed through quasi-experimental or experimental studies using observational data.